Distribuição espacial, plano de amostragem sequencial e dinâmica populacional de Anthonomus grandis Boheman (Coleoptera: Curculionidae) em algodoeiro - Grigolli, José Fernando Jurca [UNESP] (2015)
The cotton boll weevil Anthonomus grandis is the main pest of cotton crop worldwide, and the knowledge of its bioecology and distribution is essential to carry out sampling and determine the right time of your control. The main purpose of this study was to evaluate the population dynamics, vertical and spatial distribution of A. grandis and prepare a sequential sampling plan for this pest. The experiments were conducted in two seasons, 2012/13 and 2013/14, at the Experimental Station of the Foundation MS, in Maracaju, MS, in a field of 10,000 m2, divided into 100 plots of 10 x 10 m. The cultivar used was FM 993, seeded 80 cm rows apart. For the crop development were used fungicides, herbicides and growth regulators, except insecticides. Five plants per plot were weekly evaluated and recorded the number of flower buds with feeding and oviposition punctures, and adults of A. grandis in each part of five plants (upper, middle and lower). To dispersion study of A. grandis in the area, the following indexes were used: variance/mean ration, Morisita index, Green coefficient and k exponent of negative binomial distribution. To study the probabilistic models that describes the spatial distribution of insects, adjustments to Poisson and Negative Binomial distributions were tested. The sequential sampling plan was based on Maximum Likelihood Reason Sequential Test, and used the threshold level of 10% of attacked flower buds (feeding + oviposition) and the security level of 5% of attacked flower buds (feeding + oviposition). The values of type I and type II errors used was 0.05, the most suitable for insect studies. The spatial distribution of flower buds with feeding and oviposition was aggregate up to 85 DAE, with best fit to the Negative Binomial distribution, and as of this date was random, with best fit to the Poisson distribution. Adults of A. grandis are randomly distributed in the area, with best fit to Poisson distribution throughout ...